The Lack of Regulations on Restitution and Compensation for Victims of Sexual Violence Against Women and Children As A Basis for Just Legal Reformulation - Wardatul Asriah; Marhaeni Ria Siombo (CV. Green Publisher Indonesia, 2026)
This study aims to analyze legal regulations and gaps in norms, and to formulate legal reforms related to restitution and compensation for victims of sexual violence against women and children in the Indonesian legal system. The research method used is normative juridical with a statutory and conceptual approach. The results of the study indicate that although victims' rights to restitution and compensation have been recognized in various laws and regulations, such as the Sexual Violence Crime Law, the Child Protection Law, and the Witness and Victim Protection Law, the regulations are still partial and not comprehensively integrated. There are gaps in norms and legal issues, including unclear restitution execution mechanisms, the absence of standards for calculating victim losses, weak state compensation schemes, and disharmony between regulations. These conditions create a gap between normative regulations and implementation in the field, such that victims' rights are not optimally fulfilled. Therefore, a victim-oriented legal reformulation is needed through strengthening restitution execution mechanisms, establishing a state compensation fund, developing victim loss standards, and harmonizing laws and regulations to achieve substantive justice for victims of sexual violence against women and children.